Factors Predicting Stress among Final-year Students in Sirindhorn College of Public Health - Prin Yoomuang; Santipong Sripanithan; Kanjanachaya Sirijoti (YCAB Publisher, 2026)
Background: Final-year students are at a critical turning point, involving significant life changes. This is particularly true for health science students. These factors can lead to stress, negatively impacting their academic achievement and quality of life. Objective: To investigate the stress levels and predictors among students of the Sirindhorn College of Public Health, which has campuses located throughout Thailand. Method: Cross-sectional study was conducted among 321 final-year students of the diploma of public health programmes, the bachelor of health science programmes. The data were collected by using a questionnaire with a Cronbach’s alpha coefficient of 0.905. The data were analysed with descriptive statistics in terms of number, percentage, mean, and standard deviation, and stepwise multiple regression analysis was used to test the predictions. Results: The students’ stress, teaching management, extra-curricular activities, and environment in the college were found at moderate level (77.6%, 68.2%, 60.4%, and 56.7%, respectively) whereas their expectations, social support, and resilience were at high level (82.2%, 80.1%, and 63.9%, respectively), and their depression was at low level (86.6%). The predictors of stress in the sample group showed that depression (β = 0.528), resilience (β = -0.294), and extra-curricular activities (β = 0.097) could co-predict stress by 40.5% at a significance level of 0.05. Conclusion: The students experienced moderate stress, influenced by both depression (positive predictor) and resilience (negative predictor). Surprisingly, extracurricular activities increased stress. Colleges should monitor depression, foster resilience, and carefully manage stress-related extracurriculars to improve student well-being and academic performance. Keywords: stress; academic stress; final-year students; College of Public Health